Patterns of germline and somatic mutations in 16 genes associated with mismatch repair function or containing tandem repeat sequences - Shih‐Ching Chang; Yuan‐Tzu Lan; Pei‐Ching Lin; Shung‐Haur Yang; Chien‐Hsing Lin; Wen‐Yi Liang; Wei‐Shone Chen; Jeng‐Kai Jiang; Jen‐Kou Lin (Cancer Medicine)
Abstract Background We assumed that targeted next‐generation sequencing (NGS) of mismatch repair‐associated genes could improve the detection of driving mutations in colorectal cancers (CRC) with microsatellite instability (MSI) and microsatellite alterations at selected tetranucleotide repeats (EMAST) and clarify the somatic mutation patterns of CRC subtypes. Material and methods DNAs from tumors and white blood cells were obtained from 81 patients with EMAST(+)/MSI‐high (MSI‐H), 78 patients with EMAST(+)/microsatellite stable (MSS), and 72 patients with EMAST(−)/MSI‐H. The germline and somatic mutations were analyzed with a 16‐genes NGS panel. Results In total, 284 germline mutations were identified in 161 patients. The most common mutations were in EPCAM (24.8%), MSH6 (24.2%), MLH1 (21.7%), and AXIN2 (21.7%). Germline mutations of AXIN2, POLE, POLD1, and TGFBR2 also resulted in EMAST and MSI. EMAST(+)/MSI‐H tumors had a significant higher mutation number (205.9 ± 95.2 mut/MB) than tumors that were only EMAST(+) or MSI‐H (118.6 ± 64.2 and 106.2 ± 54.5 mut/MB, respectively; both P < .001). In patients with AXIN2 germline mutations, the number of pathological somatic mutations in the tumors was significantly higher than those without AXIN2 germline mutations (176.7 ± 94.2 mut/MB vs 139.6 ± 85.0 mut/MB, P = .002). Conclusion Next‐generation sequencing could enhance the detection of familial CRC. The somatic mutation burden might result from not only the affected genes in germline mutations but also through the dysfunction of downstream effectors. The AXIN2 gene might associate with hypermutation in tumors. Further in vitro experiments to confirm the causal relationship is deserved.